A COMPREHENSIVE REVIEW OF MOLNUPIRAVIR, NOVEL ANTIVIRAL DRUG FOR COVID-19 - SHUKLA, AJAY KUMAR; MISRA, SAURAV (International Journal of Current Pharmaceutical Research, 2025)
Effective oral antiviral drugs are still lacking despite improvements in COVID-19 management. Finding efficient and safe treatment against COVID-19 has become more important as a result of the discovery of novel SARS-CoV-2 mutations and the reporting of individuals with severe illness. A well-known viral RdRp inhibitor called molnupiravir has remarkably mutagenic effects on viral RNA. In the ongoing hunt for innovative antiviral drugs with acceptable efficacy and safety profiles against COVID-19, RdRp has been a priority target due to its significant role in the replication and transcription process of SARS-CoV-2 RNA. The possible evidences of efficacy and safety of molnupiravir in the treatment of COVID-19 are explored in the current review.